Factors Associated with Unmet Need for Family Planning among Married Reproductive Age Women in Toke Kutaye District, Oromia, Ethiopia. (27th March 2021) - G/Meskel, Abebe Tadesse; Desta, Habtamu Oljira; Bala, Elias Teferi
Abstract : Background . It is estimated that more than 142 million married women in developing countries have an unmet need for family planning. This study is aimed at identifying factors associated with the unmet need of family planning among married women of reproductive age in Toke Kutaye district, Ethiopia in 2019. Methods . A community-based cross-sectional study was conducted in Toke Kutaye district from March 1–30, 2019. A systematic random sampling technique was used to select 494 reproductive-age women who were married during data collection. Data were collected using a pretested structured questionnaire. Bivariate and multivariate logistic regression analyses were used to assess factors associated with the unmet need of family planning at 95% CI with a p value of ≤ 0.05. Result . The prevalence of unmet need for family planning in the Toke Kutaye district was 23.1% [95% CI (19.2-26.7)], with 15.2% for spacing and 7.9% for limiting. Women's education [AOR, 3.64, 95% CI: 1.43-9.25], number of living children [AOR, 2.63, 95% CI: 1.37-5.05], husband disapproval of family planning [AOR, 3.68, 95% CI: 2.20-6.16], and discussion with healthcare providers on family planning [AOR, 0.20, 95% CI: 0.13-0.37] were significantly associated with unmet need for family planning. Conclusion . The prevalence of unmet need for family planning was high. Therefore, program managers, partners, and health workers should work to address the gaps in maternal education, the number of living children, partner disapproval of family planning, and discussion on family planning issues through enhancing female education, awareness on family planning, and male involvement in family planning services.